PENGARUH PEMBERIAN PROBIOTIK DARI MIKROBA LOKAL TERHADAP KUALITAS INDEKS ALBUMEN, INDEKS YOLK, DAN WARNA YOLK PADA UMUR TELUR 10 HARI - Arista Pribadi; Tintin Kurtini; Sumardi . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this research were to know 1) the effect of probiotic local microbial to quality of albumen index, yolk index and yolk color; 2) the optimal of probiotic level in feed against to albumen index, yolk index and yolk color. The research was conducted on December 20th 2014-- January 19th 2015 in CV.Varia Agung Jaya , Varia Agung Village, Seputih Mataram Sub district, Central Lampung regency. Manufacture of probiotic from local microbial was made on 8 to 19 December 2014 at the Laboratory of Microbiology Faculty, University of Lampung. This research used completely randomized design (CRD) with four probiotic treatments of local microbial (0%, 1%, 2% and 3%) with 5 replications and use 40 layers. The data were analyzed with the assumptions of variance. Based on these result it can be concluded that probiotic local microbial (0%, 1%, 2% and 3%) was not significant (P> 0.05) on the quality of albumen index, yolk index and yolk color. (Keywords: Probiotic, Albumen index, Yolk index and Yolk color).